Beyond the ice: shifts in productivity and carbonate oversaturation at the Eocene–Oligocene transition - Allyson Viganò; Claudia Agnini (Scientific Reports)
Abstract During the Eocene–Oligocene Transition (EOT; 34 Ma), Earth’s climate shifted from a warm, unglaciated state to a colder, glaciated state, marked by the formation of large dynamic ice sheets on Antarctica. For decades, it was believed that calcareous nannoplankton showed little response to this transition, or where change was documented, it appeared to occur ~ 500 kyr before the EOT, suggesting that these key primary marine producers had a limited reaction to this climate transition. Here, we present morphometric and abundance data for the Clausicoccus subdistichus group from various sites across the Indian Ocean (Ocean Drilling Program [ODP] Site 756), Pacific Ocean (International Ocean Discovery Program [IODP] Site U1509; ODP Site 1209), and Atlantic Ocean (IODP Site U1411). Our findings reveal a synchronous increase in placolith size and abundance (acme interval) of this taxon. These records, investigated in different depositional settings worldwide, confirm the global nature of this event, at least at low to middle latitudes. Remarkably, this event serves as a distinctive global fingerprint of the EOT, even in poorly preserved sediments. We propose that the observed changes were primarily driven by oversaturation of carbonate ions [CO3 2−] in seawater and progressive eutrophication of the oceans, culminating in the “Early Oligocene Glacial Maximum” (EOGM).